2003
DOI: 10.1164/rccm.200209-1027oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypoxia and Lipopolysaccharide on Nitric Oxide Synthase-2 Expression in Acute Lung Injury

Abstract: The potential role of nitric oxide synthase-2 (NOS2) in acute lung injury (ALI) has gained increasing attention. This study evaluates the effects of hypoxia, an important feature of ALI, on NOS2 expression in a rat model of ALI caused by exposure to hypoxia and LPS. Exposure to hypoxia alone had no effect on the expression of NOS2 in rat lungs. LPS treatment resulted in a significant increase in NOS2 in the lungs, which was further enhanced by concomitant exposure to hypoxia. Immunohistochemical analysis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 72 publications
5
27
0
2
Order By: Relevance
“…In addition, the low systemic NO strongly suggests that there was no overt inflammatory response to the surgery or OLV. This is consistent with previous results from in vivo models of hypoxia where it has been shown that hypoxia alone does not affect inducible NOS (NOS2) [18]. Increased NOS2 expression requires other inflammatory stimuli such as lipopolysaccharide or IFN-␥.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the low systemic NO strongly suggests that there was no overt inflammatory response to the surgery or OLV. This is consistent with previous results from in vivo models of hypoxia where it has been shown that hypoxia alone does not affect inducible NOS (NOS2) [18]. Increased NOS2 expression requires other inflammatory stimuli such as lipopolysaccharide or IFN-␥.…”
Section: Discussionsupporting
confidence: 93%
“…For example, low doses of LPS following ischemia/reperfusion of gut in the rat converted moderate lung dysfunction into advanced organ failure (Koike et al, 1992). Agorreta et al (2003) showed in rat macrophages that H/R, which itself does not upregulate expression of inducible nitric oxide synthase (iNOS), can enhance LPS-induced upregulation of iNOS. Regarding the priming the response to I/R by sepsis, Colletti and Green (2001) demonstrated that lung and liver injury in rats was significantly increased when LPS was injected prior to hepatic I/R, as compared to I/R alone.…”
Section: Discussionmentioning
confidence: 99%
“…We have also identified the lung as the major site that produces NO, which is toxic to the lung [28]. Several experimental studies have indicated that the release of NO via iNOS is responsible for oxidative stress and lung injury following smoke inhalation [29], exposure to ozone [30], carrageen treatment [31], acute hypoxia [32], acid aspiration [33] and endotoxaemia [34][35][36][37]. In a murine model of sepsis, Razavi et al [38] proposed that up-regulation of iNOS in the lung caused neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%